Lexical richness in academic papers: a comparison between studentsâ€™ and lecturersâ€™ essays - Djiwandono, Patrisius Istiarto (Universitas Pendidikan Indonesia, 2016)
In the area of writing, research has yet to explore EFL learnersâ€™ ability to use varied vocabulary. Although vocabulary teaching has enriched learnersâ€™ knowledge of lexical items, whether they can use the words they have learned remains to be seen. It is important, therefore, to investigate their lexical richness in their academic writing. Lexical richness, defined as the presence of different words in a text, is commonly measured through type-token ratio (TTR). The present study set out to identify the lexical richness of senior students by comparing them to academic papers written by their lecturers. There are four objectives: (1) to determine the difference between the type-token ratio (TTR) in studentsâ€™ essays and that in their lecturersâ€™ essays; (2) to determine the difference between the use of 2000-word level (henceforth K2) in studentsâ€™ essays and that in their lecturersâ€™ essays; (3) to determine the difference between the use of academic words in studentsâ€™ essays and that in their lecturersâ€™ essays; (4) to determine the difference between the studentsâ€™ essays and their lecturersâ€™ in terms of the use of words other than the 2000-word level and the academic words (designated â€œoff-list wordsâ€). The essays written by the respondents were submitted to a website for vocabulary profiling (http://www.lextutor/ca/vp). This analysis shows that the lecturers fare better in terms of TTR and academic words, but write slightly fewer 2000-word level and off-list words than their students. While the differences in TTR and academic words are significant, the differences in the use of 2000-word level and off-list are not significant. The subsequent discussion addresses possible causes of these differences, and offers some implications for the teaching of vocabulary and writing.